Climate Change Impacts on Rainfall Variability and Adaptive Reservoir Operation in a Multi-Reservoir System - Leda, Alexander; Tahir Lopa, Rita; Maricar, Farouk; Karamma, Riswal (Civil Engineering Journal, 2025)
Changes in rainfall patterns driven by climate change have altered the hydrological regime of river basins, creating substantial challenges for water resources management, particularly in the operation of the Batutegi cascade system comprising the Batutegi Dam, Way Sekampung Dam, Argoguroh Weir, Margatiga Dam and Jabung Weir. This study assesses the impacts of climate change on rainfall intensity, dependable flow, and water allocation modeling within the Sekampung River Basin. The analysis employed five rainfall datasets downscaled from the NASA Earth Exchange Downscaled Climate Projections at 30 arc-seconds (NEX-DCP30) and simulated using five CMIP6 models for both the historical period (1980–2014) and future projections (2024–2100). Results indicate that CMIP6 projections reproduce rainfall patterns reasonably well during January–February and May–July, but perform less consistently in March–April and October–November. Most models tend to overestimate the mean annual rainfall. Rainfall variability contributes to pronounced fluctuations in river discharge, particularly during the dry season. Dependable flows show marked changes, especially within the exceedance probability range of Q10% to Q100%. Although an overall increasing rainfall trend is observed, the system is still able to satisfy water demand under the 2023 operating rules, with potential deficits persisting during critical periods. Optimization modeling further demonstrates the necessity of adaptive reservoir operation rules under climate change, which could improve the reliability of meeting multisectoral demands to approximately 80%. These findings underscore the importance of incorporating climate model projections into watershed-based water resources management to strengthen resilience against extreme hydroclimatic variability.